Rapid analysis of temperature fields in electronic enclosures based on the finite difference thermal resistance network method - Xiaoyue Zhang; Yinmo Xie; Bing Liu; Yingze Meng; Kewei Sun; Guangsheng Wu; Jianyu Tan (Case Studies in Thermal Engineering)
With the accelerated pace of functional updates and iteration in electronic enclosures design, the thermal design cycle is continuously shortened. However, the computational process of numerical simulation methods based on the finite element method (FEM) and finite volume method (FVM) is time-consuming, which limits the speed of product development. To enhance thermal design efficiency, this paper introduces the finite difference method (FDM) into the thermal resistance network model, establishing a three-dimensional thermal resistance network model for the electronic enclosure and employing an implicit difference scheme to solve its temperature field. Firstly, an experimental system for thermal analysis of a phase transition module was constructed to verify the feasibility of this model. The results demonstrate that the finite difference thermal resistance network model provides good accuracy, with a maximum average error of only 6.78 %. Subsequently, the model was applied to conduct thermal analysis on different functional modules and was compared with the FVM approach. The results indicate that this model not only accurately represents the temperature field but also controls the maximum relative error within 5 %, achieving a 99.67 % reduction in calculation time. This model can provide a valuable reference for future thermal design and temperature field predictions.